2011
DOI: 10.1159/000332057
|View full text |Cite
|
Sign up to set email alerts
|

Combining Brain Diagnosis and Therapy in a Single Strategy: The Safety, Reliability, and Cost Implications Using Same-Day versus Separate-Day Stereotactic Procedures

Abstract: Background: A therapeutic radiosurgery procedure usually follows a separate diagnostic stereotactic procedure after days or weeks. Objectives: To define the clinical reliability, safety, and cost implications of same-day diagnostic stereotactic biopsy and therapeutic radiosurgery. Methods: During an 8-year interval, 26 patients underwent stereotactic brain biopsy followed by immediate therapeutic stereotactic radiosurgery in a single-day combined procedure. The intraoperative diagnosis was determined using sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…3). 14,26,33 Debates Although the beneficial effect of radiation in the treatment of craniopharyngiomas has been well recognized, 2 critical issues remain sources of significant controversy: 1) the merits of GTR versus subtotal resection followed by irradiation given the surgical morbidity and mortality rates associated with aggressive resection and 2) the role of RT immediately after resection without first monitoring for tumor progression and the role of RT in the absence of resection (up-front or salvage treatment).…”
Section: Cyst Development and Enlargement During Radiation Therapymentioning
confidence: 99%
“…3). 14,26,33 Debates Although the beneficial effect of radiation in the treatment of craniopharyngiomas has been well recognized, 2 critical issues remain sources of significant controversy: 1) the merits of GTR versus subtotal resection followed by irradiation given the surgical morbidity and mortality rates associated with aggressive resection and 2) the role of RT immediately after resection without first monitoring for tumor progression and the role of RT in the absence of resection (up-front or salvage treatment).…”
Section: Cyst Development and Enlargement During Radiation Therapymentioning
confidence: 99%
“…Adverse radiation rates in larger case series have ranged from 6.2-10.9%, most commonly hypopituitarism, followed by visual deficits and hypothalamic obesity [83,86]. Furthermore, radiation therapy may not address the cystic component of craniopharyngiomas, which may require surgical intervention in the form of stereotactic or neuroendoscopic drainage beforehand or at the time of radiation in cases of large cysts causing symptoms [89][90][91].…”
Section: Radiationmentioning
confidence: 99%
“…Additional information pamphlet and contact information was provided for further concerns. Park et al [33] (2011) Not reported. Au et al [14] (2016) Patients were given a prescription for analgesia and a steroid taper, along with written instructions for pain control, possible adverse symptoms, and follow-up.…”
Section: Surgical Outcomesmentioning
confidence: 99%
“…A therapeutic radiosurgery procedure usually follows a separate diagnostic stereotactic procedure after days or weeks. Park et al, [33] conducted a prospective study to define the clinical reliability, safety, and cost implications of same-day diagnostic stereotactic biopsy and therapeutic radiosurgery. The intraoperative diagnosis correlated with the final histopathological diagnosis in 96% of the patients with no biopsy-related morbidity.…”
Section: Home Carementioning
confidence: 99%